Faktor-Faktor yang Mempengaruhi Pengambilan Keputusan Petani Melakukan Usaha Tani Bawang Merah (Allium Cepa Var. Aggregatum) di Desa Sumillan Kecamatan Alla Kabupaten Enrekang - Indra Wardana; Yusriadi Yusriadi; Arman Arman (Universitas Muslim Maros, 2023)
In Alla District perspective, the highest production increase was dominated by shallots from several existing leading commodities. This was due to the decision of farmers to switch commodities to farming shallots. The decision of farmers to switch farming depends on the awareness of farmers to maximize their farm income. The more farmers who decide to plant shallots, the more production will increase. This study aims to determine: What factors influence the decision making of farmers to do shallot farming (2) What factors are the most influential simultaneously on the decision making of farmers to do shallot farming in Sumillan Village, Alla Subdistrict, Enrekang Regency. This study uses a quantitative descriptive research method, because the implementation includes data, analysis and interpretation of the meaning of the data obtained. The data used are primary and secondary data. There were 50 samples in this study and then processed using SPSS 24. Analysis using multiple regression analysis techniques. From the research results obtained: that the variables that influence the decision making of shallot farmers are internal factors with variables income, and capital. While external factors, the variables are selling price. The most influential variable partially is the income variable because it has a hinger T arithmetic value than other variables.